1993
DOI: 10.1111/j.1365-2249.1993.tb03447.x
|View full text |Cite
|
Sign up to set email alerts
|

Subsets of CD8+, CD57+ cells in normal, healthy individuals: correlations with human cytomegalovirus (HCMV) carrier status, phenotypic and functional analyses

Abstract: SUMMARYTwo different subsets of CD8+, CD57+ cells have been defined, one expressing high levels (CD8W0+(CD57+)), the other expressing low levels of surface CD8 (CD81o0+(CD57+)). Increased numbers of CD8,gh+(CD57+) cells correlated with previous HCMV infection. By three-colour fluorescence analysis, the CD8high+(CD57+) population expressed T cell markers such as CD3 and CD5, and most were axf T cell receptor (afi TCR)-positive. A significant proportion also expressed CD71 (transferrin receptor) and MHC class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(24 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…CMV-infected individuals have enriched populations of CD57 + T cells and NKG2C + CD57 + NK cells (21)(22)(23)(24). In accordance with these studies we found expanded subsets of CD8 + CD57 + T cells and NKG2C + and NKG2C + CD57 + NK cells prior to EBV infection among PBMC of our CMV + 2-y-old children (Fig.…”
Section: High Frequencies Of Cd8 + Cd57 + T Cells In CMV + 2-y-old Chsupporting
confidence: 76%
See 3 more Smart Citations
“…CMV-infected individuals have enriched populations of CD57 + T cells and NKG2C + CD57 + NK cells (21)(22)(23)(24). In accordance with these studies we found expanded subsets of CD8 + CD57 + T cells and NKG2C + and NKG2C + CD57 + NK cells prior to EBV infection among PBMC of our CMV + 2-y-old children (Fig.…”
Section: High Frequencies Of Cd8 + Cd57 + T Cells In CMV + 2-y-old Chsupporting
confidence: 76%
“…The CMV-driven differentiation of T and NK cells involves acquisition of distinct functional profiles. In the case of cytotoxic T cells this includes lower activation threshold and higher degranulation and cytokine production capacity as well as bystander responses, whereas this is not always the case for NK cells (22,25,26). Therefore, an expansion of specific subsets of effector cells in CMV + individuals could affect the quality of subsequent responses toward other infectious agents as previously suggested (27,28).…”
Section: E Pstein-barr Virus Infection Is Commonly Contracted Inmentioning
confidence: 90%
See 2 more Smart Citations
“…Some studies have defined CD8 þ T cells with expression of CD57 as replicatively scenescent T cells, 19 whereas others demonstrate these cells to be effector cytotoxic T cells that are increased in infections or neoplasms and represent a chronically activated state. [20][21][22][23][24] Still, others have shown that expansions of CD8 þ /CD57 þ T cells are seen with increased frequency in the elderly, and they have postulated defects in immune system homeostasis leading to expansion of these T cells and diminished immune system surveillance. 25 Nonetheless, we are not aware of significant studies on T cells with the phenotype of CD8 þ (dim)/CD57 þ expression.…”
Section: Discussionmentioning
confidence: 99%